Keragaman Penghayatan Kristologis dalam Alkitab - Malla Sinha Dora br Ginting; Cheterine Charoline; Malita Ariana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article analyzes the depiction of Jesus Christ from various scriptural perspectives and examines the impact of the diversity of Christological experiences on Christian faith. Research shows that the Bible presents a varied picture of Jesus: Mark's Gospel presents Him as the Suffering but Powerful Servant; Matthew as the Messianic King and Great Teacher; John as the eternal Logos (Word); and Revelation depicts Him through symbols of glory as King, Judge, and Redeemer. The diversity of Christological experiences produces positive impacts in the form of deeper understanding, theological enrichment, and facilitation of interfaith dialogue. However, this diversity also has the potential to cause misunderstandings, theological conflicts, and identity crises if not properly understood. This article also explores how cultural and historical backgrounds significantly influence interpretations of Jesus, from the first-century Jewish context to contemporary interpretations in various global cultural contexts. In conclusion, although understandings of Jesus continue to evolve according to context, it is important for people to maintain their theological identity while remaining open to various enriching perspectives.